Tendencies Toward the Application of Digital Technology for Administration in the Local Administrative Organizations: The case study of the municipalities in Khon Kaen Smart City Area - Kamudhamas, Jackrit (KKBS Journal of Business Administration and Accountancy, 2022)
This research article aims to investigate the tendency and pattern of digital technology application for the administration of the five municipalities in a pilot area implementing the Khon Kaen Smart City phase 1. The study collected the primary data by interviewing the key informants categorized into three groups, including (1) local executive at policy level (2) officials at the operational level, and (3) private firm and technological entrepreneur. Additionally, related texts and information were analyzed by using documentary research along with thematic analysis as analytical techniques. The results have found that the five municipalities have trended to apply the digital technology enhancing their LAOs’ administrative capabilities. Their main objectives are to increase the efficiency of internal administration and to improve the quality of life of the citizens as users of public services. The objectives have corresponded to policy directions of the central government, the rapid changes and disruption in socio-economic conditions and public values of the 21st-century society, and the emerging awareness in technology that empowers the living of different demographics in the aging society. In conclusion, the principal factor that encourages the municipalities to be more digitalized is that they trust the power of digital technology in providing a better internal administration’s performance of the LAOs. Namely, to be faster, convenient, economical, and efficient, which will significantly affect the development of quality public goods and services they are responsible for. However, it has emphasized that the Khon Kaen Municipality has the highest degree of digital technology application, considering a qualitative dimension of its administration. Khon Kaen Municipality has shown its digital technology application into a diverse aspect of its organizational management, having a broader scope and complexity of services. This digitalization of the local administration would have resulted from a pioneership and visionary leadership of an organization, budgetary and economic competitiveness, and multilateral collaborative network.